Influence of exposure scenario on pesticide toxicity in the midge Kiefferulus calligaster (Kieffer) - Domingues, Inês
In aquatic environments, many factors determine the overall impact of a toxic event, constituting "exposure scenarios" that must be understood so that risk assessment strategies can be successfully applied. In this work, an experimental design was planned to investigate the influence of the organism age, duration of exposure and subsequent recovery period (after cessation of toxic exposure) on chlorpyrifos or carbendazim toxicity to Kiefferulus calligaster. The endpoints studied were cholinesterase (ChE) activity and glutathione S-transferase (GST) activity. The influence of age and exposure time and the existence of recovery depend on the chemical and the biomarkers tested, suggesting that no general rule can be applied when trying to assess overall toxicity of pesticides and that detailed knowledge has to be acquired on a case-to-case basis. (C) 2007 Elsevier Inc. All rights reserved.